THE EFFECTIVENESS OF PROMOTIONAL STRATEGIES IN INCREASING SALES OF TRADITIONAL FOOD MSMES IN CIAMIS - Lati, Lati Sari Dewi (LKP DCI, 2025)
AbstractThis study aims to evaluate: The promotional strategies implemented by traditional food MSMEs in Ciamis Regency; The sales volume achieved by these MSMEs; and The impact of promotional strategies on sales volume. Using a descriptive quantitative method with a sample of 65 respondents selected through total sampling, the study reveals that: The promotional strategies employed by traditional food MSMEs in Ciamis Regency are effective; The sales volume of these MSMEs is satisfactory; and Promotional strategies have a positive and significant effect on sales volume, with a coefficient of determination of 37.7%. This indicates that promotional strategies account for 37.7% of the variation in sales volume, while the remaining 62.3% is influenced by other factors not explored in this study. The findings suggest that while promotional strategies play a crucial role, additional research is needed to identify other factors impacting sales volume.